MENCIPTAKAN KEUNTUNGAN BISNIS MELALUI STRATEGI CUSTOMERS PROFITABILITY BERDASARKAN ACTIVITY-BASED COSTING - Wiwi Idawati (Jurnal Akuntansi Bisnis, 2017)
Massive changes occurring in the environment are giving effects to the business environment too,which causes cultural changes along with significant increase to the cost of living. More severe competition in the business should be faced by the companies with better ways of conducting the operations in order that competitive advantageous. One way to boost profi usually done by companies is to increase the sales, the idea of which lies on the traditional volume-related concept. The concept leads companies to accept products orders from customers without first investigating which will bring profit and which will not. This activity based costing system is able to calculate more accurately and precisely the cost that will go to the customers. The approach exercises the activities and costs consumed by each customer in calculating which will be preserved and which will be ended. The result is more efficient operation cost that enhances the profit.  Key words: Business profit, customers profitability, Traditional costing system,  Activity based costing system